A new approach for deducing the stage-discharge relationship of a triangular broad-crested device. (June 2022) - Nicosia, Alessio; Ferro, Vito
Abstract: In this paper, the outflow process of a triangular broad-crested device is examined using the dimensional analysis and the incomplete self-similarity theory. A new theoretical stage-discharge relationship is proposed, and its applicability is verified using measurements available in literature. The proposed power equation is characterized by a coefficient depending on device apex angle and a constant value of the exponent. Highlights: A power theoretical stage-discharge relationship of the device is proposed. The coefficient of the stage-discharge depends on device apex angle. The coefficient of the stage-discharge equation is constant. The errors in discharge estimate are not systematic and are normally distributed.